Using a health belief model to assess COVID-19 vaccine intention and hesitancy in Jakarta, Indonesia - Hidayana, Irma (2023)
Since January 2021, Indonesia has administered a nationwide COVID-19 vaccination. This study examined vaccine intention and identified reasons for vaccine hesitancy in the capital city of Jakarta. This is a cross-sectional online survey using the Health Belief Model (HBM) to assess vaccine intent predictors and describe reasons for hesitancy among Jakarta residents. Among 11,611 respondents, 92.99% (10.797) would like to get vaccinated. This study indicated that all HBM constructs predict vaccine intention (P< 0.05). Those with a high score of perceived susceptibility to the COVID-19 vaccine were significantly predicted vaccine hesitancy (OR = 0.18, 95% CI: 0.16-0.21). Perceived higher benefits of COVID-19 vaccine (OR = 2.91, 95% CI: 2.57-3.28), perceived severity of COVID-19 disease (OR: 1.41, 95% CI: 1.24-1.60), and perceived susceptibility of the current pandemic (OR = 1.21, 95% CI: 1.06-1.38) were significantly predicted vaccination intend. Needle fears, halal concerns, vaccine side effects, and the perception that vaccines could not protect against COVID-19 disease emerged as reasons why a small portion of the respondents (n = 814, 7.23%) are hesitant to get vaccinated. This study demonstrated a high COVID-19 vaccine intention and highlighted the reasons for vaccine refusal, including needle fears, susceptibility to vaccine efficacy, halal issues, and concern about vaccine side effects. The current findings on COVID-19 vaccination show that the government and policymakers should take all necessary steps to remove vaccine hesitancy by increasing awareness of vaccine efficacy and benefit interventions.